Construction of the ACDE Ring System of Calyciphylline A-type Alkaloids via Intramolecular Diels–Alder Reaction of a Tetrasubstituted Olefin - Nakamura, Hugh; Kawakami, Manami; Tsukano, Chihiro; Takemoto, Yoshiji (Synlett, 2019)
A concise synthesis of the ACDE tetracyclic ring system of calyciphylline A-type alkaloids was investigated. The intramolecular Diels–Alder reaction of a tetrasubstituted olefin with furan enabled the construction of the ACD ring system bearing two contiguous quaternary carbons in one step, and subsequent intramolecular [3+2] cycloaddition successfully gave the E ring.
Keywords: Daphniphyllum alkaloid; calyciphylline A; Diels–Alder reaction; tetrasubstituted olefin